Effect of the Cu-rich precipitates on thermal conductivity of RPV model steel. Issue 11 (2nd November 2019) - Li, Niannian; Feng, Liu; Yin, Fengshi; Zhao, Ertuan
ABSTRACT: Cu-rich precipitates are the important influence factors for the irradiation embrittlement of the reactor pressure vessel model steels. The microstructure of the Cu-rich precipitates could be revealed by mechanical and magnetic properties. In this article, the effect of the Cu-rich precipitates on thermal conductivity was studied. The reactor pressure vessel (RPV) model steels were aged for different time at 500°C. The results show that the thermal conductivity of RPV model steel is first decreased and then increased during the experiment, with a minimum value at 48.33 ± 0.21 W·m −1 ·K −1 after being aged for 200 h. The changing thermal conductivity is decided by the synergistic effect of the following three factors: (1) the crystal structure transformation of Cu-rich precipitates, (2) the orientation relationship between the matrix and Cu-rich precipitates, (3) the content of Cu atoms in the matrix.